Noise monitoring in CNC machine working area in electronic based company in Kuantan, Malaysia - Nur Nazwa Syamimi, Salleh (2017)
Noise is the most significant health hazard to the working population in terms of the number of people affected has been recognized by the World Health Organization (WHO). The noise induced hearing loss is the most cases damage accumulates over time. Therefore, the goal of noise control regulation for company TT Electronics is not more than 85 dB (A). In this project, the noise level monitoring is important to do as the result from the Audiometric Test for the employees exposed to the noise is has been made. There are 15 machines involved at the CNC Machine area with a different type of process and model of machines that will affect the noise level. The Sound Level Meter (SLM) is use as the instrument to measure the noise level in dB (A) along with the software SE323 that can analyst from the noise level from the SLM. In SE323, the average of the noise level can be seen in certain time and it is easier to use. There are few spot of noise indicates the high noise level through the experiment. The noise level can exceed to more than 100 dB (A). The cause of the noise level at this spot is because of the leakage which is pneumatic pressure, stripping process and others. The noise level at the idle time is 53.21 dB (A) with the effect of air conditioner and others but not from the machine. Furthermore, the noise level at the different distance from the SLM to the source of noise is quite low compared to the noise level at the source of noise with the difference 0.6 dB (A). Thus, the shorter the distance an employee from the source of noise, the higher the noise level. In addition, the noise average at the technician point is 94.71 dB (A) for the 8 hour shift. Hence, the noise level regulations at this company are compared to the noise level regulation of OSHA and it shows that noise level at this company is exceeding the noise level regulation of OSHA. Consequently, the noise control should be implementing to prevent the more problem to employee especially of hearing loss.